ANALISIS PENERAPAN GMP PADA PRODUK KERIPIK UBI JALAR DI KOTA JAYAPURA - Novita Condro; Gatot B Santoso (Universitas Pattimura, 2017)
Crackers industry in Indonesia is mostly home industry or small and medium business enterprises, which produces crackers in a traditional way. Therefore, the quality of the product must be well maintained and meet the requirements as stated in the government regulation N0. 28. 2004 about safety, quality and nutrition of the food. Several small and medium food businesses in Jayapura has still not implement hygiene and sanitation during processing of the product. Thus, the aims of this study were to analyze and to identify the food safety of sweet potato crackers produced by small and medium business in Jayapura city whether it goes in accordance with Indonesia National Standard of Quality; to determine the level of application of Good Manufacturing Practice (GMP) of sweet potato crackers produced by home industries in Jayapura. A descriptive analysis was applied in this research by using an interview and observation to obtain information regarding processing, basic suitability of GMP, also an experimental design was applied to determine the quality of the product. Result showed that there was still limited implementation of GMP among small and medium enterprises. There were 4 home industries that produce sweet potato crackers which did not meet the criteria specified in SNI No 01-4306-1996 due to the positive contamination of the product with Escherichia coli as.